Pengaruh Return on Equity dan Earning Per Share terhadap Harga Saham (Studi Kasus pada Perusahaan Indeks LQ45 yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2017) - Dida Farida Latipatul Hamdah; Lina Nurlela; Risma Diani (Jurnal Wacana Ekonomi, 2019)
The purpose of this study was to determine the effect of return on equity (ROE) and earnings per share (EPS) on stock prices on the LQ45 index listed on the Indonesia Stock Exchange. The research method used in the preparation of this thesis is an associative method with a quantitative analysis approach, while the analysis used is multiple regression analysis techniques and classical assumption tests. Based on the research results of hypothesis testing using multiple regression analysis, it shows that simultaneously, return on equity (ROE) and earnings per share (EPS) have a significant effect on stock prices. Partially, return on equity (ROE) has a significant effect on stock prices as well as earnings per share (EPS) which has a significant effect on stock prices.